1992
DOI: 10.1002/ajh.2830390302
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype and DNA content of myeloma cells in primary plasma cell leukemia

Abstract: To clarify the biological characteristics of the myeloma cells in primary plasma cell leukemia (PCL), we studied the immunological phenotype and DNA content of cells from five patients with primary PCL as compared to those from the patients with typical multiple myeloma (MM). In two of five patients with PCL myeloma cells had B-cell-associated antigens (B1, J5) and surface immunoglobulin in addition to plasma cell associated antigens, suggesting that these cells are immunologically immature as compared to matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Analysis of immunoglobulin gene revealed the presence of both heavy and K light chain rearrangements, but the TCR-P and bcl-2 genes remained in germ line configuration. Surface markers of leukemic cells analyzed as previously described [2] revealed that CD38 and adhesion molecules such as CDlla, C D l l b , CDllc, CD44 and CD54 were positive. We also evaluated the response of the leukemic cells to various cytokines by the 3H-thymidine uptake method [3].…”
Section: Case Reportmentioning
confidence: 99%
“…Analysis of immunoglobulin gene revealed the presence of both heavy and K light chain rearrangements, but the TCR-P and bcl-2 genes remained in germ line configuration. Surface markers of leukemic cells analyzed as previously described [2] revealed that CD38 and adhesion molecules such as CDlla, C D l l b , CDllc, CD44 and CD54 were positive. We also evaluated the response of the leukemic cells to various cytokines by the 3H-thymidine uptake method [3].…”
Section: Case Reportmentioning
confidence: 99%
“…3,4,68 For example, the loss of the tumor suppressor gene TP53 on chromosome 17p13, is a common event, as it is observed in 50% and 75% of pPCL and sPCL, respectively. 9 Overexpression of MYC genes due to copy number alterations in chromosome 8 is also common, and it distinguishes PCL from MM.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low incidence, most publications on PCL are based on single case reports. Little is known about the immunophenotype of tumor cells in primary PCL because very few reports have looked at the evaluation of single antigens expression on bone marrow or peripheral blood plasma cells [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%